Sound engineering explained - Talbot-Smith, Michael (Focal Press, 2002)
This straightforward introduction to audio techniques guides the beginner through principles such as sound waves and basic acoustics and offers practical advice for using recording and reproduction equipment. Previously known as Audio Explained, this latest edition includes new material on: reverberation and its use in recording; principles of digital mixing; digital recording; including MiniDisc and MP3; digital artificial reverberation. Designed with the student in mind, information is organised according to level of difficulty. An understanding of the basic prin.